Gene expression profiling of SARS-CoV-2 infections reveal distinct primary lung cell and systemic immune infection responses that identify pathways relevant in COVID-19 disease. Issue 2 (18th December 2020) - Moni, Mohammad Ali; Quinn, Julian M W; Sinmaz, Nese; Summers, Matthew A
Abstract: To identify key gene expression pathways altered with infection of the novel coronavirus SARS-CoV-2, we performed the largest comparative genomic and transcriptomic analysis to date. We compared the novel pandemic coronavirus SARS-CoV-2 with SARS-CoV and MERS-CoV, as well as influenza A strains H1N1, H3N2 and H5N1. Phylogenetic analysis confirms that SARS-CoV-2 is closely related to SARS-CoV at the level of the viral genome. RNAseq analyses demonstrate that human lung epithelial cell responses to SARS-CoV-2 infection are distinct. Extensive Gene Expression Omnibus literature screening and drug predictive analyses show that SARS-CoV-2 infection response pathways are closely related to those of SARS-CoV and respiratory syncytial virus infections. We validated SARS-CoV-2 infection response genes as disease-associated using Kaplan–Meier survival estimates in lung disease patient data. We also analysed COVID-19 patient peripheral blood samples, which identified signalling pathway concordance between the primary lung cell and blood cell infection responses. Graphical Abstract: GRAPHIC 1: SARS-CoV-2 graphical abstract depicting the study workflow and analysis pipeline. (A ) We first conducted phylogenetic and RNAseq analyses comparing SARS-CoV-2, SARS, MERS, and influenza strains, and the overlapping gene expression effects of infection with these viruses. (B –C ) Datasets from a study of transcriptional effects of SARS-CoV-2 infection in human lung epithelial cells (profiled using RNAseq) was analysed to determine differential gene expression. (D ) Gene ontology and curated cell signalling pathway databases were used to screen the differentially expressed gene list for functional enrichment. (E ) SARS-CoV-2 genes were used for drug prediction and survival analyses in disease datasets, results suggesting pathology associated genes and pathways for subsequent functional analysis. (F ) A targeted immune profile in SARS-CoV-2 infected patient blood samples was analysed to assess system wide immune effects of infection.